Customer's perception towards product and location of @: works department at Hankyu Jaya Klang / Raja Rohafiza Raja Hassan - Raja Hassan, Raja Rohafiza (1997)
Nowadays the growth of retail industry is indeed unprecedented. Several megamalls are expected to open in time for the Commonwealth Games in 1998; this include the KLCC, Berjaya Star City, Mid Valley, Plaza Rakyat and Bintang Square. As it has very good prospect in customer mind, it will get the customers attention very well. Retailing is only one kind of marketing -the last link in the marketing chain of distributors, beginning with the producer and\ the ending with the consumer. Retailing activities include, purchasing goods and services for sale, storing, display pricing, advertising) selling, financing, servicing and others activities necessary to complete the sale with buyer. The goal of retailing is to make profit by servicing the need and wants of consumers for product and services. Thus the key to making profit in retailing rests with the retailer's ability to serve "targeted" groups of consumers. Successful retailers select the kind of consumers they aim to serve, and these consumers become the target population - the people whom they buy merchandise or design services.